Palm kernel shell as potential fuel for syngas production - Umar, H.A. (Springer Science and Business Media Deutschland GmbH, 2020)
This study investigated the elemental content, proximate analysis, morphological nature, calorific value and ultimate analysis of the Elaeis guineensis palm kernel shell (PKS), to determine its suitability for use in syngas generation. The elemental content was studied using the X-ray fluorescence spectroscopy (XRF) analysis, and the presence of elements like Ca, Fe, Si, K and P with their oxides was detected. Field emission scanning electron microscopy (FESEM) with energy dispersive electron microscopy (EDX) was applied to detect the structural properties of PKS, with details of light surface elements. The PKS has a porous structure for a free flow of air and volatile matter, and carbon and oxygen were seen as the major surface elements, 64 and 29.4, respectively. It had a high calorific value of 18.84Â MJ/kg. The ultimate analysis revealed suitable contents of carbon 48.4, oxygen 45 and hydrogen 5.85. The proximate analysis showed the presence of high volatile matter of 73.4, low moisture of 6.0 and ash content of 5.8. Overall, PKS has a good prospect to be used as a fuel for syngas production via gasification. Â© Springer Nature Singapore Pte Ltd 2020.